Kesantunan Berbahasa dalam Jejaring Sosial Twitter sebagai Bahan Pembelajaran Berbicara di Kelas IX MTs Assalam Ciruas - Romdhoningsih, Diana (Universitas Mathla'ul Anwar Banten, 2019)
This study aims to gain an in-depth understanding of language politeness in twitter social networking. This research, will provide theoretical benefits and practical benefits. This study, used a qualitative descriptive method for the process of collecting and analyzing data. The subject of this research is through the twitter account of Basuki Tjahaja Purnama @basuki_btp as the politeness user in the twitter social network taken from June to August 2015. Data analysis techniques selected ini this study are content analysis. The results of this study are the politeness of the language contained in the social networking twitter account @basuki_btp during Juneof August 2015 is wisdom maxim as much 7 utterances (3 violations and 4 implement), generosity 3 utterances maxims, award maxim 1 speech, maxim agreement 1 speech, and maxim sympathy 1 utterance, whilw the language politeness that was most violated on the twitter account @basuki_btp during June-August 2015 was the maxim of wisdom, wich was as many as 3 utterances. The results of the analysis in this study can be used as an alternative learning material to speak in class IX especially on speaking skills.